Teaching and learning of English academic writing in a public university in Malaysia: a case study - Razali, Abu Bakar; Azmar, Khairunnisa (Modestum, 2024)
English academic writing is deemed as essential skills to be acquired by students in tertiary education as they are mostly assessed through their proficiency in writing skills. To teach this technical course, ESL lecturers need to possess the required content knowledge and pedagogical skills. However, many ESL/EFL lecturers and students regard academic writing as challenging to teach and learn. This paper aims to discuss the teaching and learning of English academic writing in a public university in Malaysia. Grounded in a small-scale case study, data were collected through semi-structured interviews, focus group discussions (FGD), and classroom observations with one ESL lecturer and four undergraduate students participated in the study. Data were analysed thematically using thematic analysis where themes and codes were used to explain the findings. Findings revealed that teacher-centered approach with heavy-reliance on textbook teaching was used to teach English academic writing and students learned academic writing by engaging in lots of drills and writing practices. The paper suggests ESL lecturer to adopt traditional teaching approach with process-based approach as a dual approach in teaching English academic writing and modifications and changes should be made to the syllabus of academic writing at tertiary education level.